The Influence of Digital Marketing, Marketing Communication, and Sustainability Awareness on Product Competitiveness - Finta Aramita; Indawati Lestari; Nasrullah Hidayat; Wansuryani Wansuryani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In today’s globalized business environment, SMEs must strengthen human resources, adopt technology, and leverage digital marketing to enhance product visibility, sustainable awareness, and competitiveness. This research aims to determine and analyze the effect of digital marketing and marketing communication on the competitiveness of SMES’ products through sustainable awareness of SME players. The sample was 130 respondents. The data analysis in this study uses path analysis to provide a clearer and more comprehensive picture of how various factors affect the competitiveness of SMEs and how marketing strategies can be optimized. These results show that digital marketing and marketing communication have a positive and significant effect on sustainable awareness and product competitiveness. The implications of this research emphasize the importance of digital marketing and marketing communication in increasing sustainable awareness and competitiveness of SMES’ products. The implementation of this research provides training on digital marketing and marketing communication to SMES players, facilitates access and use of digital platforms for SMEs, and implements effective marketing communication strategies to strengthen sustainable awareness.